2003
DOI: 10.1110/ps.0229403
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of conserved asparagine and arginine residues from the N‐terminal region in the catalytic mechanism of rat liver and Trypanosoma cruzi tyrosine aminotransferases

Abstract: Rat liver and Trypanosoma cruzi tyrosine aminotransferases (TATs) share over 40% sequence identity, but differ in their substrate specificities. To explore the molecular features related to these differences, comparative mutagenesis studies were conducted on full length T. cruzi TAT and N-terminally truncated rat TAT recombinant enzymes. The functionality of Arg315 and Arg417 in rat TAT was investigated for comparison with the conserved Arg292 and Arg386 in aspartate and bacterial aromatic aminotransferases (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Since hTAT showed transamination activity toward glutamate, phenylalanine as well as tyrosine (Sivaraman and Kirsch, 2006), kinetic parameters of mTAT toward these three amino acids were also tested and calculated (Table 1). Based on the mTATsubstrate specificity, mTAT behaves in a manner similar to hTAT, in that it has a narrow substrate specificity compared to tcTAT (Nowicki et al, 2001; Sobrado et al, 2003; Sivaraman and Kirsch, 2006; Donini et al, 2009). TcTAT, on the other hand, has broad substrate specificity; in particular, it has an affinity to alanine, which differs considerably from tyrosine, the primary substrate of mTAT and hTAT (Nowicki et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hTAT showed transamination activity toward glutamate, phenylalanine as well as tyrosine (Sivaraman and Kirsch, 2006), kinetic parameters of mTAT toward these three amino acids were also tested and calculated (Table 1). Based on the mTATsubstrate specificity, mTAT behaves in a manner similar to hTAT, in that it has a narrow substrate specificity compared to tcTAT (Nowicki et al, 2001; Sobrado et al, 2003; Sivaraman and Kirsch, 2006; Donini et al, 2009). TcTAT, on the other hand, has broad substrate specificity; in particular, it has an affinity to alanine, which differs considerably from tyrosine, the primary substrate of mTAT and hTAT (Nowicki et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…However the enzyme has the highest activity in the liver. In hTAT, the first 38 amino acids may not be involved in enzyme dimerization, and are not required in the active site stability and enzyme-substrate interactions (Sobrado et al, 2003). This N-terminal fragment, however, is required for being targeted by the ubiquitin-proteosome pathway (Gross-Mesilaty et al, 1997), which degrades proteins to small peptides (Ciechanover et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…by site‐directed mutagenesis found that R57A and R57Q mutations in rat tyrosine aminotransferase abolished its activity completely. Mutation in analogous residues of T. cruzi TAT , N17S, and R20A/Q led to lowered catalytic efficiency of mutated variant significantly . Therefore, the authors hypothesize that the N‐terminal region of LdTAT that has few identical residues may hold the reason for co‐substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Arg-417 is one of the residues responsible for the interaction of Tyr with mouse and rat TyrAT (Sobrado et al, 2003;Mehere et al, 2010), and Arg-390 of PsTyrAT might perform the same function. As reported for other investigations of plant aminotransferases, the in vitro activity of PsTyrAT was not affected by the addition of exogenous PLP.…”
Section: Involvement Of Tyrat In Bia Metabolism In Opium Poppymentioning
confidence: 99%
“…Although Tyr, Phe, and Trp are primarily involved in protein synthesis, a vast array of secondary metabolites are also derived from these aromatic amino acids (Tzin and Galili, 2010). Although the biochemical and structural characterization of tyrosine aminotransferase (TyrAT) in mammals and fungi is well established (Blankenfeldt et al, 1999;Sobrado et al, 2003;Schneider et al, 2008;Mehere et al, 2010), considerably less is known about these enzymes in plants. TyrAT is regulated by coronatine, wounding, and methyl jasmonate (MeJA) and has been implicated as the initial enzyme in tocopherol biosynthesis in Arabidopsis (Arabidopsis thaliana) plants (Lopukhina et al, 2001;Holländer-Czytko et al, 2005) and Amaranthus caudatus and Chenopodium quinoa cell cultures (Antognoni et al, 2009).…”
mentioning
confidence: 99%